a ) \(A=\left(3x+7\right)\left(2x+3\right)-\left(3x-5\right)\left(2x+11\right)\)
\(A=6x^2+9x+14x+21-6x^2-33x+10x+55\)
\(A=76\)
Vậy ........
\(B=\left(x^2-2\right)\left(x^2+x+1\right)-x\left(x^3+x^2-3x-2\right)\)
\(B=x^4+x^3+x^2-2x^2-2x-2-x^4-x^3+3x^2+2x=-2\)
Vậy.........
\(D=x\left(2x+1\right)-x^2\left(x+2\right)+x^3-x+3\)
\(D=2x^2+x-x^3-2x^2+x^3-x+3=3\)
Vậy ......
\(E=\left(x+1\right)\left(x^2-x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\)
\(E=x^3+1-x^3+1=2\)
Vậy ..........
\(a,A=\left(3x+7\right)\left(2x+3\right)-\left(3x-5\right)\left(2x+11\right)\)
\(=6x^2+9x+14x+21-6x^2-33x+10x+55\)
\(=76\)
Vậy biểu thức A không phụ thuộc vào biến
\(b,B=\left(x^2-2\right)\left(x^2+x-1\right)-x\left(x^3+x^2-3x-2\right)\)
\(=x^4+x^3-x^2-2x^2-2x+2-x^4-x^3+3x^2+2x\)
\(=2\)
Vậy biểu thức B không phụ thuộc vào biến
\(c,D=x\left(2x+1\right)-x^2\left(x+2\right)+x^3-x+3\)
\(=2x^2+x-x^3-2x^2+x^3-x+3\)
\(=3\)
Vậy biểu thức D không phụ thuộc vào biến
\(d,E=\left(x+1\right)\left(x^2-x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\)
\(=x^3+1-x^3+1\)
\(=2\)
Vậy biểu thức E không phụ thuộc vào biến